Understanding Blood versus Blond Orange Consumption: A Cross-Cultural Study in Four Countries - Giménez-Sanchís, Adrián; Zhong, Kui; Pintor-Jardines, Aurora; Farina, Vittorio; Besada, Cristina (MDPI, 2022)
Understanding consumer perceptions and attitudes to specific fruit is key information for not only increasing fruit consumption, but also for marketing reasons. It may also give clues to breeders to set quality objectives. This study explores different aspects that help to explain blood vs. blond orange consumption: availability and consumption habit, satisfaction attributes, facilitators and consumption barriers, consumption contexts, expectations and purchase intention. The study was conducted in China, Mexico, Spain and Italy, where citrus fruit consumers were invited to respond an online questionnaire. Our results revealed Italy as the country with the highest availability and consumption of blood oranges, followed by China, Mexico and Spain. “Liking” and “healthy properties” were the most important reasons for consumption irrespectively of orange type, but certain differences among countries were detected in secondary reasons. In all the countries, “juicy” was the most relevant attribute for consumer satisfaction, followed by flavour/taste attributes. “Aromatic” and “unfibrous” were substantial requirements for Italians and Chinese, while Spaniards attached importance to the blood oranges colour. Regarding consumption contexts, “eat with salt or chilly powder” was specific for Mexico, while “to improve health”, “as a gift” or “at a restaurant” were contexts mainly cited in China. Despite taste preferences for other fruit being the main consumption barrier in all the countries for both orange types, the relevance of other barriers depended on culture and orange type. Mexican participants seemed to take a more neophobic attitude to blood oranges, while “inconvenient” was reported as a barrier for consuming blond ones in Spain and China. We conclude that blond and blood oranges can co-exist on markets at a high consumption rate, as in Italy. Specific interventions are needed in other countries because consumer attitudes to oranges, mainly blood ones, depend on culture.